TOURISM TRANSFORMATION, EDUCATION, AND THE PRODUCTION OF SOCIAL VULNERABILITY IN BATU CITY, INDONESIA - Nurhadi, Iwan; Amiruddin, Lutfi (Erudio Journal of Educational Innovation, 2026)
Tourism-led development is widely viewed as a catalyst for economic growth, yet its social implications remain underexamined. This study investigates how tourism restructuring shapes labor precarity and social vulnerability in Batu City, Indonesia, with particular attention to education. Using a qualitative approach, data were collected through in-depth interviews and focus group discussions with tourism workers, community members, and local stakeholders. Findings indicate that tourism expansion increases informal, flexible, and seasonal employment, resulting in income insecurity, extended working hours, and limited social protection. Educational disparities reduce workers’ capacity to adapt to changing labor demands, reinforcing social inequality. By linking labor transformation, education, and vulnerability, this study extends sociological perspectives on tourism and provides evidence for policies promoting inclusive labor conditions, educational opportunities, and sustainable tourism development.